2018
DOI: 10.1016/j.ijggc.2018.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the impact of CO2 storage in sandstone formations by experimental studies and geochemical modeling: The case of the Mesohellenic Trough, NW Greece

Abstract: Representative sandstone samples from Mesohellenic Trough (NW Greece) were selected to investigate the geochemical reactions that occur when they come in contact with CO 2 under representative in-situ conditions (T=70 o C, P=150bar, 6 months reaction in batch experiments). Those sandstones consisted of predominant calcite and quartz, with lesser amounts of feldspars, chlorite, ankerite, dolomite, kaolinite, montmorillonite and muscovite. After reaction with CO 2 , the brine became acidic and was enriched in ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…These results show that the sandstones examined include relatively higher quartz contents and less calcite compared to those located in the Mesohellenic Trough [73]. Furthermore, effective porosity of the Klepa Nafpaktias sandstones, as it was calculated through the total porosity, which is about 6% for the Group I presents higher values of effective porosity in contrast to the other two sandstone groups and tend to be lower than the Pentalofos sandstones of the Mesohellenic Trough~9%.…”
Section: A Potential Scenario For Storage Of Co 2 In Sandstones From mentioning
confidence: 66%
See 2 more Smart Citations
“…These results show that the sandstones examined include relatively higher quartz contents and less calcite compared to those located in the Mesohellenic Trough [73]. Furthermore, effective porosity of the Klepa Nafpaktias sandstones, as it was calculated through the total porosity, which is about 6% for the Group I presents higher values of effective porosity in contrast to the other two sandstone groups and tend to be lower than the Pentalofos sandstones of the Mesohellenic Trough~9%.…”
Section: A Potential Scenario For Storage Of Co 2 In Sandstones From mentioning
confidence: 66%
“…This case presents many similarities with that described for the Mesohellenic Trough (NW Greece), which examined the potential of CO 2 storage within porous sandstones that are overlaid be a less permeable cap rock formation [71][72][73]. In the latter case, a depth of over 800 m was regarded as suitable for trapping CO 2 under supercritical conditions [73][74][75]. The sandstone samples provided from our study are highly comparable in terms of composition with sandstones from the Pentalofos formation of the Mesohellenic Trough [72].…”
Section: A Potential Scenario For Storage Of Co 2 In Sandstones From mentioning
confidence: 71%
See 1 more Smart Citation
“…Vatalis et al [73] proposed the storage of CO 2 in the known deposit of zeolite in Evros (Northern Greece). Koukouzas et al [74] concluded that the Pentalofos and Tsotyli sandstone formations could be a potential CO 2 storage site under specific conditions. This approach needs further investigation.…”
Section: Co 2 Storage In Greecementioning
confidence: 99%
“…[66][67][68] Another deposit could be zeolite according to Vatalis 2012 69 and also the sandstone formations according to Koukouzas 2018. 70 Finally, it was investigated the role of water carbonation of forsterite in scCO2 and found that the reactions could be more extensive under specific conditions. 71…”
Section: Minerals For Potential Co 2 Storagementioning
confidence: 99%